Optimalisasi Kekerasan Baja ST-42 Melalui Karburasi Ramah Lingkungan Berbasis Biokarbonat Cangkang Kepiting dan Modulasi Suhu Tempering - Semuel M.J.S Tuny; H. S. Latumaerissa; Erwin B Pattikayhatu; Nevada Nanulaitta; Graciadiana I Huka (Jurusan Teknik Mesin, 2025)
ST-42 low-carbon steel inherently possesses limitations in its surface mechanical properties, particularly regarding hardness and wear resistance. This study aims to enhance the material's functionality through pack carburizing and tempering heat treatments, utilizing the innovation of crab shell waste which is rich in Calcium Carbonate (CaCO3) as a biogenic catalyst to replace the toxic synthetic Barium Carbonate (BaCO3). The carburizing process utilized a mixture of walnut shell charcoal and 30% crab shell powder, followed by rapid quenching in SAE 20-50 oil, and subsequent tempering at varying temperatures from 200°C to 600°C. Hardness was evaluated using the Rockwell (HRC) method. The results demonstrated that the integration of the crab shell catalyst accelerated the Boudouard reaction via massive CO2 emissions, significantly increasing the surface hardness by 22.80% to an average of 138.34, compared to a mere 10.49% increase achieved without a catalyst. During the tempering phase, heating within the 200°C – 400°C range resulted in a marginal hardness decrease due to the formation of fine carbide particles that maintained wear resistance while relaxing residual stresses. Conversely, extreme heating at temperatures between 500°C – 600°C caused a drastic hardness reduction down to 125.325, driven by the dissolution of the rigid martensite structure into a ductile ferrite phase, accompanied by carbon spheroidization. In conclusion, crab shells are highly effective as an eco-friendly energizer that drastically boosts carbon diffusion, while modulating the tempering temperature provides precise control over the material's hardness-to-ductility balance. Keyword : St-42 low-carbon steel, pack carburizing, crab shell, tempering, Rockwell (HRC) method